2003
DOI: 10.1029/2001jd001222
|View full text |Cite
|
Sign up to set email alerts
|

Urban aerosol radiative properties: Measurements during the 1999 Atlanta Supersite Experiment

Abstract: [1] As part of the Atlanta Supersite 1999 study, aerosol radiative and related physical and chemical properties are examined on the basis of measurements of PM 2.5 (aerosol particles with aerodynamic diameters, D p , less than 2.5 mm) in urban Atlanta. In addition to potential compliance issues with proposed regulatory standards, PM 2.5 concentrations in Atlanta and the surrounding region are large enough to have an important impact on atmospheric radiative transfer and hence visibility and potentially regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 75 publications
9
62
4
Order By: Relevance
“…However, our σ sp average value is relatively larger than the average values measured by Pereira et al (2008), at Evora, Portugal (46 Mm −1 ), and by Vrekoussis et al (2005), in remote areas of Greece and Turkey (50 and 45 Mm −1 ). Nevertheless, the measured σ sp values at Granada are lower than those obtained in highly polluted areas in US (Greenwald et al, 2007;Carrico et al, 2003) and are much smaller than those observed in large urban areas in Asia (Bergin et al, 2001;Andreae et al, 2008;Garland et al, 2008;Ganguly et al, 2006). These results indicate that Granada aerosol scattering coefficient values are typical of moderately polluted urban areas.…”
Section: Aerosol Scattering Absorption Coefficients and Aerosol Numbementioning
confidence: 39%
See 1 more Smart Citation
“…However, our σ sp average value is relatively larger than the average values measured by Pereira et al (2008), at Evora, Portugal (46 Mm −1 ), and by Vrekoussis et al (2005), in remote areas of Greece and Turkey (50 and 45 Mm −1 ). Nevertheless, the measured σ sp values at Granada are lower than those obtained in highly polluted areas in US (Greenwald et al, 2007;Carrico et al, 2003) and are much smaller than those observed in large urban areas in Asia (Bergin et al, 2001;Andreae et al, 2008;Garland et al, 2008;Ganguly et al, 2006). These results indicate that Granada aerosol scattering coefficient values are typical of moderately polluted urban areas.…”
Section: Aerosol Scattering Absorption Coefficients and Aerosol Numbementioning
confidence: 39%
“…The single scattering albedo values obtained in Granada are similar to the mean value of 0.68±0.07 obtained by Eidels-Dubovoi (2002) at Pedregal site in Mexico City. Nevertheless, the single scattering albedo measured in Granada is lower than those obtained in Marseille, France, (0.85±0.05), Toulon, France, (0.73±0.07 to 0.79±0.07), Atlanta (0.87±0.08), Beijing, China, (0.81±0.08) and Guangzhou, China, (0,82±0.05) by Mallet et al (2003), Saha et al (2008), Carrico et al (2003), Bergin et al (2001) and Andreae et al (2008), respectively. The lower values of single scattering albedo in an urban area are generally related to black carbon, although dust can also contribute to aerosol light absorption (Bohren and Hoffman, 1983;Horvath, 1998).…”
Section: Scattering Angström Exponent Aerosol Single Scattering Albementioning
confidence: 72%
“…However, b ext in this study was 1.2-3.7 times that reported in summer in Guangzhou, China (419/Mm), in Nanjing, China (249/Mm), and in Atlanta, United States (137/Mm) (Carrico et al, 2003;Jung et al, 2009;Shen et al, 2014). As discussed in Section 2.1, the annual median visibility seemed to improve less with the significant drop of PM 2.5 mass concentrations in recent years.…”
Section: Annual Trend Of Light Extinction Coefficient (B Ext )contrasting
confidence: 43%
“…For aerosol samples collected in APEX-E2, sample filters were heated in an electric furnace at 300 C in ambient air for 30 minutes to remove OC and then used to determine the elemental carbon content (EC) (Ohta and Okita 1984). Though such a combustion method is famous to estimate mass concentration of EC, several studies Schmid et al 2001;Clarke et al 2002;Carrico et al 2003) suggested that this method can overestimate the mass concentration of EC if OC chars at low temperature and produces EC. Such an artifact was likely to be a possible reason for overestimating mass concentrations of EC.…”
Section: Aerosol Optical Thickness (Aot)mentioning
confidence: 99%
“…Analysis of EC is one of the most difficult challenges facing atmospheric chemists (Hering et al 1990;Huebert and Charlson 2000). Mass concentration of EC depends strongly on the analytical method (e.g., Schmid et al 2001;Carrico et al 2003). For aerosol samples collected in APEX-E2, sample filters were heated in an electric furnace at 300 C in ambient air for 30 minutes to remove OC and then used to determine the elemental carbon content (EC) (Ohta and Okita 1984).…”
Section: Aerosol Optical Thickness (Aot)mentioning
confidence: 99%